2018
DOI: 10.1007/s00198-018-4426-8
|View full text |Cite
|
Sign up to set email alerts
|

Prior fragility fracture and risk of incident ischaemic cardiovascular events: results from UK Biobank

Abstract: Prior fragility fracture is an independent risk factor for incident ischaemic cardiovascular events in men. Further work may clarify whether this association is causal or represents shared risk factors, but these findings are likely to be of value in risk assessment of both osteoporosis and cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…The observed association between incident fractures and MACE in CKD is novel in nephrology but is in line with recent evidence in the general population indicating a bidirectional relationship between CVD and poor bone health [ 29–31 , 44 , 45 ]. A recent meta-analysis found consistency across published studies with regard to CVD risk in patients with low (versus high) bone mineral density [pooled HR 1.33 (95% CI 1.27–1.38)] or a history of fractures [HR 1.25 (95% CI 1.05–1.48)] [ 45 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The observed association between incident fractures and MACE in CKD is novel in nephrology but is in line with recent evidence in the general population indicating a bidirectional relationship between CVD and poor bone health [ 29–31 , 44 , 45 ]. A recent meta-analysis found consistency across published studies with regard to CVD risk in patients with low (versus high) bone mineral density [pooled HR 1.33 (95% CI 1.27–1.38)] or a history of fractures [HR 1.25 (95% CI 1.05–1.48)] [ 45 ].…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have focused mostly on in-hospital and short-term mortality [ 8 , 20 , 25–28 ], leaving long-term mortality largely unexplored in CKD. Another plausible consequence of fractures is ischaemic cardiovascular disease (CVD), as recently suggested by general population studies [ 29–32 ]. We are not aware of studies evaluating the association between incident fractures and subsequent cardiovascular events in CKD patients, but we find this hypothesis conceivable given the features of CKD-MBD.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies confronted these findings, concluding that there is no relationship between smoking and OA [86,87]. Direct mechanical joint injury also can cause acute inflammation, increase the production of IL-1β and IL-6 and chronic post-traumatic OA, low mobility and CVD [88,89].…”
Section: Distinct Risk Factors For Cvd and Oamentioning
confidence: 99%
“…Hip fracture has also been shown to be associated with increased risk of cardiovascular events (2,(13)(14)(15)(16). For example, a Denmark study showed that the one-year adjusted hazard ratio (aHR) of stroke and myocardial infarction (MI) for hip fracture patients was 2.23 and 2.34 respectively, when compared to the general population (16).…”
Section: Introductionmentioning
confidence: 99%